TAM Perception of Teachers to Students' Learning Outcomes in Table Tennis Lesson - Ugi Nugraha; Ekawarna Ekawarna; Muhammad Ali; Try Arianto Adhanegara (Universitas Pendidikan Ganesha, 2022)
The development of science and technology is increasingly rapid and penetrates into all aspects of life. One of the efforts to utilize technology is to use a variety of existing technologies in maximizing ongoing learning such as in PJOK learning (physical education, sports, and health). The purpose of this study is to analyse of teaching staff or teachers in order to maximize technology in teaching and learning activities, so that physical education, sports and health can run optimally. The sampling technique used in this study was purposive sampling with total of 42 teachers. This research uses (mixed method) with explanatory design. The instrument of this study used a learning outcome question sheet and an observation sheet. The results of this study are teachers of PJOK subjects are more dominant with good categories based on gender, namely male teachers are superior and based on the range of years of service, namely teachers with a work period of 1-8 years are superior and the technology acceptance model (TAM) on teachers has an influence which is significant to student learning outcomes on the material of table tennis sports. Then the technology that continues to develop provides convenience in teaching and learning activities for physical education, sports and health lessons.